2001
DOI: 10.1021/bi010141t
|View full text |Cite
|
Sign up to set email alerts
|

The Human Interferon- and Estrogen-Regulated ISG20/HEM45 Gene Product Degrades Single-Stranded RNA and DNA in Vitro

Abstract: The human ISG20/HEM45 gene was identified independently on the basis of its increased level of expression in response to either interferon or estrogen hormone. Notably, the encoded protein is homologous with members of the 3' to 5' exonuclease superfamily that includes RNases T and D, and the proofreading domain of Escherichia coli DNA polymerase I. We provide here direct biochemical evidence that Isg20 acts as a 3' to 5' exonuclease in vitro. This protein displays a pH optimum of approximately 7.0, prefers Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
126
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(139 citation statements)
references
References 25 publications
13
126
0
Order By: Relevance
“…In accordance with this information, a site-specific aspartate to glycine residue mutation in the ExoII conserved motif of ISG20 (mut-ISG20D94G; Fig. 1A) abolished its activity (24). Because IFN causes a strong induction of ISG20 expression (21,29), these data suggested that the protein could be an active player in the antiviral action mediated by IFNs against RNA viruses.…”
Section: Isg20 Confers Resistance To Vsv Infection In Transientlysupporting
confidence: 65%
See 3 more Smart Citations
“…In accordance with this information, a site-specific aspartate to glycine residue mutation in the ExoII conserved motif of ISG20 (mut-ISG20D94G; Fig. 1A) abolished its activity (24). Because IFN causes a strong induction of ISG20 expression (21,29), these data suggested that the protein could be an active player in the antiviral action mediated by IFNs against RNA viruses.…”
Section: Isg20 Confers Resistance To Vsv Infection In Transientlysupporting
confidence: 65%
“…Based on these observations, we have demonstrated that ISG20 is a 3Ј to 5Ј exonuclease in vitro with specificity for single-stranded RNA and, to a lesser extent, for DNA, suggesting that ISG20 could be involved in the antiviral function of IFN against RNA viruses (24). Notably, ISG20 is the second known RNase regulated by IFN, along with RNase L (24).…”
Section: Interferons (Ifns)mentioning
confidence: 81%
See 2 more Smart Citations
“…Mutations in the ISRE result in the loss of IFN type I and type II inducibility of the luciferase reporter gene (Gongora et al, 2000). Interestingly, it has been reported that ISG20 is a 3' to 5' exonuclease in vitro with speci®city for single stranded RNA and, to a lesser extent, for DNA (Nguyen et al, 2001). Notably, ISG20 is the second known RNase regulated by IFN, along with RNase L. In addition, over-expression of ISG20 confers resistance to infections by some RNA viruses (N Mechti, personal communication).…”
Section: Isg20mentioning
confidence: 99%